Bouquet of blooms : 15 quilts, wall hangings, and pillows. (Leisure Arts, 2011)
Flowers never go out of style, and the same is true of floral quilts. Whether you choose to use floral prints or create your flowers with appliqué or foundation piecing, there are blooms here that will fit the modern home. You can make a quilt, a wall hanging, or simply fashion a few pillows to brighten a corner.